Treasure Islands and the Islands of Buried Treasures. Loneliness and Isolation - in the Theatrical Work of the Founders of Laboratories as Well as Socially Excluded People - Magdalena Hasiuk (University of Lower Silesia, 2014)
The text presents the state of loneliness and isolation experienced in their theatrical work by the members of theatre laboratories (based on the case of the Odin Theatre) and socially excluded people (for example, those taking part in the activities of the theatre operating at the Women's Rights Centre in Warsaw). In the first part it shows how loneliness can ally itself with the dramatic artist to become an important element of his or her work method and »life in art«. The second part of the paper deals with the original practice of the therapeutic and »ritual theatre« set up by Dagna Ślepowrońska and its influence on women who have been victims of violence in their liberation from the feeling of isolation.